Formy skrócone rzeczowników francuskich oznaczających osoby - Gajos, Mieczysław (Studia Romanica Posnaniensia, 2007)
The author of this article deals with the problems of “abbreviated forms” in French, emphasising the role which this type of lexical units performs in communication. Their detailed typology, mechanisms which are their foundation and their functioning in language are performed. In his conclusion the author postulates that this kind of lexical units should be taken into consideration more comprehensively than it has been so far.